Abuse of medication during international football competition in 2010 - lesson not learned - Tscholl, P. M.; Dvorak, J. (British Journal of Sports Medicine, 2012)
Background: The use of medication in professional football has previously been shown to defy clinical guidelines. Materials and methods: Physicians of the teams who participated at the 2010 FIFA World Cup provided the list of medications used by each player within the 72 h preceding every match. Results: During the tournament 71.7% of all players took medication, and 60.3% (444 of 736 players) took painkilling agents at least once. Over a third of players (39.0%) took a painkilling agent before every game. More medications were used during the finals than during the qualifying round of matches (pool games) (0.87±0.09 vs 0.77±0.03, p<0.01). Players from North and South America took almost twice the number of medications than did players from other continents (1.18±0.08 vs 0.64±0.03; p<0.01). Conclusion: The use of medication reported by the team physicians in international football competition is increasing. Systematic use - medication for every match - appeared to be the norm in certain teams. This has implications for player health. These data encourage efforts to better understand, and to address, this potential disastrous practice in professional sports.